)Qæ(NSTORÆQ UKRAÇNSXKOÇ LÆTERATURI (BXX (NSTOLÆTTQ (B:s)E (NP)QÆDRU^NIK (B/s)E (NkN(B. 1,s (NpER[A POLOWINA (BXX (NSTOL)QÆTTQ (B/ (NREDAKTOR w(B. (Ng(B. (NdON^IKs)E - (NdON^IK(B, (Nw(B. (Ng(B.,s; (NdON^IK(B, (Nw(B.(Ng(B.,s ((NkI)QÇW (B:s)E (NlIB)QÆDX(B,s)E, 1998)
(NwISW)QÆTLENNQ LÆTERATURNOGO PROCESU WÆD PO^ATKU (BXX (NSTOLÆTTQ J DO PO^ATKU (B40-(NH ROKÆW(B.s)E
)Qæ(NM(B. (NPOKAV^(B.: (NS(B. 445-459s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NlEPKIJ b(B. (Ns(B.s; (N~UMAK w(B.s; (NtULUB z(B.s; (NmALAN@K )Qã(B.s)E; (NbUZXKO d(B.s; )Qæ(NSTORÆQ UKRAÇNSXKOÇ LÆTERATURIs)E; (NL)QÆTERATURNO(B-(NMISTECXKE VITTQs)E; (NPOEZ)QÆQs)E; (NPROZAs; (NSATIRAs; (NGUMORs; (NDRAMATURG)QÆQs)E; (NDITQ^A L)QÆTERATURAs)E; (NL)QÆTERATUROZNAW^A KRITIKAs)E